Statistical Analyses on the Seasonal Rainfall Trend and Annual Rainfall Variability in Baramati Tehsil of Pune District, Maharashtra - Rahul, Gulave Madhuri; Kamble, Praveen Narayan; Janardhan, Gadekar Deepak; Sampat, Medhe Ravindra; Palghadmal, Kalpana Vamanrao; Tukaram, Arote Somnath; Santosh, Zine Aruna (Metallurgical and Materials Engineering, 2025)
Rainfall is an extremely important environmental factor as changes in rainfall patterns have a major impact on agriculture. Understanding rainfall trends is an important tool for the development and future of agriculture. The variable attributes of climate are the annual climate temperature and precipitation, which have received a great deal of attention worldwide. The degree of variability or fluctuation of this factor varies from place to place and time to time. Therefore, it is necessary to design and examine climate science software systems in various formats to assess climate induced change and suggest adaptive strategies in countries with rain-fed agriculture attributing to a changing climate. In the present study we have studied the pattern and changes of rainfall and its distribution in Baramati Tehsil. For this research, the average rainfall period and rainfall from 2007 to 2023 have been studied. Also these correlations have been studied through statistical systems.